Znaczenie kapitału społecznego w tworzeniu sieci dostaw - Baraniecka, Anna (The Role of Social Capital in a Creation of Supply Networks, 2005)
The main aim of this report is to point specifical role of social capital in a creation and activity of network organizations, in particular - supply networks. The author is trying to argue that the above dependence really exists and determines, to a high degree, the competitiveness of the network.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1078, s. 15-26